2021
DOI: 10.24818/beman/2021.11.4-06
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Capital Adequacy Ratio and Non-Performing Loan on Profitability of Commercial Banks Listed on the Indonesia Stock Exchange in 2017-2019

Abstract: This study has the purpose to analyze the influence of Capital Adequacy Ratio and Non-Performing Loan on profitability of Commercial Banks. The sample of this study consists of 26 Commercial Banks listed on the Indonesia Stock Exchange in 2017-2019. This research used Multiple Regression Analysis to analyze the data gathered from audited financial reports of those banks. The results showed that the Capital Adequacy Ratio and Non-Performing Loan simultaneously affect the Profitability, which means that if there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Second, tier 2 (supplement) capital provides debt capital instruments, convertible debt, inter-mediate term preferred stock, etc. With the capital adequacy standard set, the greater the capital bank raises, the banking business can minimize the risk of loss and carry out its operational activities to increase business profitability (Djaya and Yanuarti, 2021). Ha1: Capital Adequacy Ratio (CAR) has a significant positive effect on profitability…”
Section: Capital Adequacy Ratiomentioning
confidence: 99%
“…Second, tier 2 (supplement) capital provides debt capital instruments, convertible debt, inter-mediate term preferred stock, etc. With the capital adequacy standard set, the greater the capital bank raises, the banking business can minimize the risk of loss and carry out its operational activities to increase business profitability (Djaya and Yanuarti, 2021). Ha1: Capital Adequacy Ratio (CAR) has a significant positive effect on profitability…”
Section: Capital Adequacy Ratiomentioning
confidence: 99%
“…However, Hakuduwal(2021) affirmed that the capital ratio of Nepalese commercial banks is not linked with profitability. Additionally, Djaya(2019) examine the influence of capital ratio on profitability of Indian banks. The study found an insignificant positive association between capital adequacy and the profitability of Indian banks.…”
Section: Capital Adequacy and Profitabilitymentioning
confidence: 99%
“…LPD tidak menggunakan seluruh potensi modalnya dalam meningkatkan profitabilitas, sehingga menyebabkan rasio CAR tidak menjadi faktor yang mempengaruhi profitabilitas LPD secara signifikan. Hasil penelitian ini sejalan dengan penelitian sebelumnya yang dilakukan oleh Widyastuti et al, (2017), Djaya & Yanuarti (2021), Kusumastuti & Alam (2019), serta Zaidanin & Zaidanin (2021) yang menemukan hasil bahwa kecukupan modal tidak berpengaruh terhadap profitabilitas.…”
Section: Hasil Dan Pembahasanunclassified